Complex formation, in vitro digestion, structural, and physicochemical properties of fish oil and wheat starch blend. Issue 11 (25th August 2020) - Desai, Ajay S.; Brennan, Margaret A.; Zeng, Xin‐An; Brennan, Charles S.
Abstract: This study aimed to examine the effect of inclusion salmon oil (SO), cod oil (CO), coconut oil (CONT) to wheat starch (WS) on pasting, textural, and in vitro starch digestibility properties. The binary component blend (BCBs) sample showed better complex index (CI) as compared to WS and WS–WG (wheat gluten) and decreased with increasing carbon chain length. The inclusion of lipids to WS significantly reduced pasting and textural characteristics than that of WS alone. In BCBs samples V type amylose–lipid complexes peak at 20°2 θ and greater short‐range molecular order were formed with fatty acids producing more crystalline structure. A similar observation was noted by FTIR, Raman, and NMR spectroscopy. Differential scanning calorimetry (DSC) results suggested that decreased in the gelatinization temperature and enthalpy after addition of different oil sources to WS. The amount of reducing sugar released during starch digestion appears to be dependent on starch hydrolysis. In this study, due to amylose–lipid complex formation, in vitro glycemic response decreased in BCBs samples followed by WS–WG with the ability to act as a barrier to suppress the activity of digestive enzymes to hydrolyze the starch molecules. This altered characteristics of WS might help to formulate the foods to overcome the digestibility concern in humans. Practical applications: The results from the present study suggested that comprehending the effect of different lipid sources blend with wheat starch on complex formation, in vitro digestion, structural, and physicochemical properties can provide a guideline regarding alteration of physicochemical and digestibility characteristics of wheat starch which inhibit the accessibility of digestive enzymes to hydrolyze the starch molecules due to amylose–lipid complex formation.